When the booze rules the family - Syrek, Ewa; Sztuka, Maria (No Limits, 2024)
The article addresses the problem of alcoholism as a phenomenon that affects not only addicts but also their loved ones, especially children. It cites troubling statistics on alcohol consumption in Poland and Europe and presents the social and psychological consequences of addiction, focusing on the experiences of adult children of alcoholics (ACAs). It also highlights the importance of therapy, self-discovery and personal development as tools for regaining control over one's life. It draws attention to the need for education, support, and breaking social taboos related to alcoholism and co-dependency. The article is based on the results of many years of research by scholars, which led to the publication of a monograph – a compendium of knowledge on how to overcome the trauma of growing up in a family affected by alcoholism.